Key performance indicators in elite beach soccer - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer, 2020)
This chapter initially provides an overview of key performance indicators in elite beach soccer that have been established in the literature. A total of 20 tactical and technical indicators were then identified to be employed in the present study. The significant indicators were then identified through principal component analysis with varimax rotation. It was demonstrated from the study that the following performance indicators, i.e. shot at front third, chances created, goals scored at the first period, goals scored at the second period, goals scored at the third period, goals scored at extra time, shot at back third, pass at back third, interception, turnover, complete save by the keeper, uncomplete save by the keeper, shot inside a box as well as shot outside box are non-trivial in evaluating the performance of a given team. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2020.